Synthetic peptides containing ITIM-like sequences of IREM-1 (CD300F) differentially regulate MyD88 and TRIF-mediated TLR signalling through activation of SHP and/or PI3K - Lee, S-M (Blackwell Science Inc, 2012)
The immune receptor expressed on myeloid cells 1 (IREM-1/CD300F) has been shown to inhibit various inflammatory processes in myeloid cells, such as macrophages and mast cells. IREM-1 exerts its inhibitory effect through its intracellular immunoreceptor tyrosine-based inhibition motifs (ITIMs). In order to generate immunomodulatory molecules that can regulate the inflammatory activation of macrophages, decapeptides representing each of the five ITIM-like sequences in the cytoplasmic tail of IREM-1 were synthesized in conjugation with human immunodeficiency virus-transactivator of transcription (HIV-TAT(48–57)), which was added to promote internalization of the peptides. Interestingly, all these TAT–ITIM fusion peptides inhibited Toll-like receptor (TLR)-mediated production of proinflammatory molecules, including matrix metalloproteinase (MMP)-9, tumour necrosis factor (TNF)-α, monocyte chemotactic protein-1 (MCP-1) and interleukin (IL)-8. When various TLR ligands were used to stimulate the human macrophage-like cell line human acute monocytic leukaemia cell line (THP)-1, the TAT–ITIM peptides blocked both myeloid differentiation factor 88 (MyD88) and Toll-interleukin 1 receptor (TIR)-domain-containing adapter-inducing interferon-β (TRIF)-mediated TLR signalling pathways. Utilization of specific inhibitors and detection of the active form of signalling adaptors by Western blot analysis further demonstrated that the inhibitory effects of these TAT–ITIM peptides require activation of Src homology 2 (SH2)-containing tyrosine phosphatase (SHP) and/or phosphoinositide 3-kinase (PI3K). These data indicate that these synthetic peptides may be used to regulate immune responses that involve TLR-mediated inflammatory activation of macrophages.